Antioxidan Activity from Methanol Extract of Kratom Leaves (Mitragyna speciosa) Maseration Result Using The DPPH Method: Aktivitas Antioksidan Ekstrak Metanol Daun Kratom (Mitragyna speciosa) Hasil Maserasi Menggunakan Metode DPPH - Andhika Dwi Aristyawan; Anggi Ayu Windari; Mercyska Suryandari; Galuh Gondo Kusumo (Akademi Farmasi Surabaya, 2023)
Antioxidants are compounds that can prevent the formation of free radicals. Kratom is a typical plant from South Putussibau area, in West Kalimantan. The kratom plant contains alkaloids, triterpenoid-steroids, saponins, tannins and flavonoids. The main component of kratom leaves is an indole alkaloid that is efficacious as an antioxidant. The goal is to determine the antioxidant activity of kratom leaf extract (Mitragyna speciosa). The method used is the measurement of the reduced amount of DPPH from an antioxidant compound UV-Vis spectrophotometrically at a wavelength of 517nm using Vitamin C as a comparison. The extraction method used is maceration. The test was sampled 10 mg of kratom leaf extract (Mitragyna speciosa) with 10 ppm, 20 ppm, 30 ppm, 40 ppm, and 50ppm concentrations, then repeated 3 times. The results of the antioxidant activity of kratom leaves (Mitragyna speciosa) were expressed with IC50 values of 44,169 ± 0.5313 with an RSD value of 1.202%. Then it can be concluded that kratom leaf methanol extract (Mitragyna speciosa) has a very strong antioxidant activity with an IC50 value of 44,169 ± 0.5313 with an RSD value of 1.202%.